Economic Program Policy BUMNIn Increasing Economic Growth In Indonesia - Rinaldi Rinaldi; Suwito Suwito; Guntur Eko Saputro (CV. AFDIFAL MAJU BERKAH, 2024)
Economic program policies towards state-owned enterprises (BUMN) in economic growth in Indonesia have become commonplace in various countries. The main reason for implementing economic program policies is to improve and streamline the performance of BUMN so that it can achieve its founding targets, namely the provision of public services for the community and profits for the state. However, this policy is often rejected due to concerns that the role of the state is minimal and the role of the private sector is too dominant, which refers to a free market system so that the interests of society are not guaranteed. The method used in this research is qualitative research with a descriptive-analysis method using relevant secondary data and normative/literature assessment using a statutory approach and a conceptual approach. The aim of this research is to provide a comprehensive understanding of economic program policies by BUMN in Indonesia, both from a historical perspective and applicable positive law. The research object is BUMN (State-Owned Enterprises). This research concludes that the majority of listed BUMNs are able to improve business performance and profit generation. Economic programs are not the only solution for state company management, but they must always be able to reform and innovate in terms of future BUMN business strategies.